2017
DOI: 10.1177/2156587217714145
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Chemical Constituents and Indications of Aromatic Waters Soft Drinks (Hydrosols) Used in Persian Nutrition Culture and Folk Medicine for Neurological Disorders and Mental Health

Abstract: In Persian nutrition culture, drinking aromatic waters (hydrosols, distillate) has a long history as functional beverages or therapeutic remedies. The co-distilled water with essential oils, which contains partial amounts of more water-soluble volatile compounds are diluted and used as beverages. Since the solubility of volatile components is different in water, the overall composition, and thus the biological activities of aromatic waters seem to be different from the essential oils they were co-distilled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
3
22
1
Order By: Relevance
“…In the hydrosol samples, the most abundant compound was trans-p-mentha-1(7),8-dien-2-ol, which represented 31.75% and 36.63% of the total hydrosol in the PS and KS, respectively. These results are consistent with the fact that hydrosols contain dissolved molecules of EO, considering that more than half of the compounds that we identified in hydrosol can also be found in the essential oil [12].…”
Section: Gas Chromatography and Mass Spectrometry (Gc-ms) Analysis Ofsupporting
confidence: 92%
See 2 more Smart Citations
“…In the hydrosol samples, the most abundant compound was trans-p-mentha-1(7),8-dien-2-ol, which represented 31.75% and 36.63% of the total hydrosol in the PS and KS, respectively. These results are consistent with the fact that hydrosols contain dissolved molecules of EO, considering that more than half of the compounds that we identified in hydrosol can also be found in the essential oil [12].…”
Section: Gas Chromatography and Mass Spectrometry (Gc-ms) Analysis Ofsupporting
confidence: 92%
“…Free volatiles were isolated in lipophilic and water fraction. Water fractions or hydrosols are condensed water vapors containing dissolved molecules of EOs and more water-soluble (polar) volatile compounds [12]. Due to the different solubility of the volatile compounds in water, the overall composition and thus the biological activity of the hydrosol differs from lipophilic fraction or essential oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that hydrosols have a more positive effect on NiTi’s corrosion resistance than have the essential oils and the extract of Celtis australis. Hydrosol or aromatic water is the aqueous phase obtained by distillation of herbs in addition to the essential oil (25). A study conducted on persian herbs demonstrated that the chemical composition of essential oils is very different from their aromatic water (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most of phenolic compounds as secondary metabolites in the plants present in natural foods may reduce the risk of important health defects because of their antioxidant properties. The origin and biochemistry of these phyto-compounds have some practical uses [5]. Secondary metabolites are synthesized in biochemical pathways that are not necessary for plant growth but have biological and pharmacological importance.…”
Section: Editorialmentioning
confidence: 99%